Influence of Different Apical Preparations on Root Canal Cleanliness in Human Molars: a SEM Study - Gianluca Plotino; Luigi Tocci; Luca Testarelli; Gianluca Gambarini (eJournal of Oral Maxillofacial Research, 2014)
Objectives: To compare the influence of type and dimensions of the apical preparation on the cleanliness of the apical area in molars.